(untitled) (The Review of Diabetic Studies, 2024)
Important technological advances in data processing and result distribution center users’ attention on the benefits gained from laboratory results. Many trends converge to implement and automate laboratory systems contributing to positive results. However, for this scenario to be realistic in the clinical scope and guarantee good results reliability, effective quality management in laboratory activity is necessary. One of the basic procedures to guarantee that results obtained in medical laboratories are of sound quality refers to the implementation and regular application of a set of quality control tests. This procedure makes it possible to monitor the quality of the results and the laboratory performance through the use of commercial control materials produced under strict parameters and normative requirements, demonstrating a characteristic behavior in a determined situation. The systematic application of these tests furnishes support to health professionals’ confidence in the results provided, guaranteeing the quality of the results. There are multiple factors affecting the clinical-technical role within the attained quality limits. Thus, besides participating in external quality control programs, auditing the whole process should be given prime importance. Data generated by the application of control materials are an outstanding source of information about the performance of the methods at the laboratory level.